P-MAPA, a Fungi-Derived Immunomodulatory Compound, Induces a Proinflammatory Response in a Human Whole Blood Model. (24th November 2020) - Gonçalves, Mariana Torrente; Squaiella-Baptistão, Carla Cristina; Pidde, Giselle; Lopes, Priscila Hess; da Silva Nunes, Iseu; Tambourgi, Denise V.
Abstract : P-MAPA is a complex compound, derived from Aspergillus oryzae cultures, that has shown immunomodulatory properties in infection and cancer animal models. Despite promising results in these models, the mechanisms of cellular activation by P-MAPA, suggested to be Toll-like receptor- (TLR-) dependent, and its effect on human immune cells, remain unclear. Using an ex vivo model of human whole blood, the effects of P-MAPA on complement system activation, production of cytokines, and the expression of complement receptors (CD11b, C5aR, and C3aR), TLR2, TLR4, and the coreceptor CD14 were analyzed in neutrophils and monocytes. P-MAPA induced complement activation in human blood, detected by increased levels of C3a, C5a, and SC5b-9 in plasma. As a consequence, CD11b expression increased and C5aR decreased upon activation, while C3aR expression remained unchanged in leukocytes. TLR2 and TLR4 expressions were not modulated by P-MAPA treatment on neutrophils, but TLR4 expression was reduced in monocytes, while CD14 expression increased in both cell types. P-MAPA also induced the production of TNF- α, IL-8, and IL-12 and oxidative burst, measured by peroxynitrite levels, in human leukocytes. Complement inhibition with compstatin showed that P-MAPA-induced complement activation drives modulation of C5aR, but not of CD11b, suggesting that P-MAPA acts through both complement-dependent and complement-independent mechanisms. Compstatin also significantly reduced the peroxynitrite generation. Altogether, our results show that P-MAPA induced proinflammatory response in human leukocytes, which is partially mediated by complement activation. Our data contribute to elucidate the complement-dependent and complement-independent mechanisms of P-MAPA, which ultimately result in immune cell activation and in its immunomodulatory properties in infection and cancer animal models.